Diversity and Ecology of Araceae in the Mossy Forest, Brinchang, Pahang, Peninsular Malaysia - Mohamad Asraf-Fizree; MZ Norhazlini; Hamzah Zulhazman (BIO Web of Conferences)
A total of ten species from seven genera of Araceae were collected from the Mossy Forest, Brinchang, Cameron Highlands, Pahang, Peninsular Malaysia. Among these, eight species are common, while two species (Arisaema brinchangense and A. filiforme) are categorized as endangered. Several common genera that thrive in lowland areas such as Aglaonema Schott., Homalomena Schott., Piptospatha N.E. Br., Schismatoglottis Zoll. & Morritz, and Scindapsus Schott., were absent. The findings show that the number of Araceae in this area is low due to the altitudinal range. This paper focuses on two highland Araceae species, A. brinchangense and A. filiforme, their unique morphological characteristics make them potential attractions for ecotourism. The paper provides updated information on these species to enhance understanding and appreciation of their importance in conservation and biodiversity. By highlighting their distinct features and status, this paper aims to raise awareness about the need for their protection and preservation, while also showcasing their potential as ecotourism assets for those interested in exploring and experiencing the rich natural heritage of highland ecosystems.